The value system of modern youth after the COVID-19 pandemic - M. S. Ashilova; O. Ya. Kim; A. S. Begalinov; K. K. Begalinova (Образование и наука)
Introduction. The COVID-19 pandemic, which spread widely around the world at the beginning of 2020, has seriously affected the educational sphere as a whole. Under the influence of the pandemic, the psychology of young people, their value orientations, thoughts about the future, their well-being and behaviour are changing. R. Inglehart notes that this process is heterogeneous and manifests itself in different ways in different countries of the world. In developed countries with a predominance of values of self-expression and secular-rational values, the pandemic has affected more painfully than in developing countries with traditional values and values of survival. This study presents how the pandemic affected the values of student youth in Kazakhstan, a country that, according to R. Inglehart’s map of cultural values, occupies a more neutral position. And also it was analysed whether the trends in Kazakhstan correlate with global ones.Aim. The present research aims to identify how the pandemic has affected the value orientations of students in Kazakhstan and other countries around the world. The main hypothesis, derived by analogy with other countries of the world, is the assertion that the pandemic has led to widespread depressions among Kazakh youth, shaking their life values and the importance of education.Methodology and research methods. The theoretical and methodological basis of the article was the research of R. Inglehart and C. Welzel, devoted to the problems of values, including in the conditions of the pandemic crisis. The survey method was also used. It was conducted on the basis of a sample formed: one thousand full-time university students from 17 regions of Kazakhstan (three megacities and 14 regions). A questionnaire containing 13 key questions concerning the values of young people, their prospects for the future, fears and anxieties, and the quality of education was used.Results. The results of this study and their comparison with similar surveys in other countries of the world allowed the authors to conclude that Kazakh students in general are experiencing the same negative consequences of the pandemic as their peers from other countries. However, in matters of life goals, educational values, career prospects and general well-being, Kazakhstani students show great resilience and a positive attitude. Based on R. Inglehart’s position, this happened due to the low economic development of the country, which, according to his system of values, is classified as developing countries with a strong traditional way of life and the predominance of survival values.Scientific novelty. The article for the first time attempts to analyse the values of Kazakh students through the prism of the concept of R. Inglehart and C. Welzel, and also shows the impact of the pandemic on the well-being, quality of education and value orientations of young people in Kazakhstan and other countries of the world. Practical significance. The materials of the article can be used to develop new approaches to teaching/educating students, taking into account the impact of the pandemic, the deterioration of the well-being of students and the crisis of values. This study reveals the specifics of these processes in Kazakhstan, one of the post-Soviet countries belonging to developing, traditional countries.